Польова математична модель турбогенератора з еквівалентованими зубцевими зонами статора і ротора - Ковівчак, Я.В. (Моделювання та інформаційні технології, 2011)
In paper the simplified field mathematical model of the turbogenerator, in which
tooth zones of the stator and rotor equivalent by continuous anisotropic medium is
proposed.